Impact of positive CD4 cells on event‐free survival in follicular lymphoma patients - Cong Li; Na Guo; Shuiyun Han; Haifeng Yu; Tao Lei; Xi Chen; Shuailing Peng; Haiyan Yang; Meijuan Wu (Cancer Medicine)
Abstract Objective Previous results about prognostic value of CD4+ T cells in follicular lymphoma (FL) remain controversial. Methods Immunohistochemistry was used to examine expression of positive CD4 cells in 103 patients with FL 1‐3A. Early failure was described as failing to achieve event‐free survival (EFS) at 12 or 24 months. Results There were 49 (47.6%) male and 54 (52.4%) females, with a median age of 54 years. Compared to patients with <20% of positive CD4 cells, patients with ≥20% of positive CD4 cells exhibited a significant lower risk of early failure (2‐year EFS rate: 56.7% vs 73.5%, p = 0.047). When patients were stratified based on positive CD4 cell combined with FLIPI, the median EFS (p = 0.002) and median OS (p = 0.007) were significantly different. Conclusions This study demonstrated that higher expression of positive CD4 cells predicts lower risk of early failure in follicular lymphoma, and combination analysis of CD4 and FLIPI could better predict disease relapse and survival outcome.